2001
DOI: 10.2139/ssrn.265362
|View full text |Cite
|
Sign up to set email alerts
|

The Long Run Performance of Privatization Related ADR Issues

Abstract: American Depositor y Receipt s (ADRs ) hav e bee n increasingl y use d i n th e Share Issu e Privatizatio n proces s (SIP ) b y privatizin g government s bot h i n developed an d developin g countries . I n thi s stud y long-ter m performanc e o f 143 privatizatio n relate d AD R program s wer e analyzed . Th e AD R program s covered i n th e stud y wer e initiate d betwee n 198 4 an d 1999 , an d include d a diverse mi x o f companie s fro m 2 9 differen t industrie s acros s 3 1 develope d a n emerging marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Schaub (2003) finds that the long-term underperformance of ADRs is greater for IPO issues than for SEO issues, and for emerging market issues than for developed market issues. Aybar (2001) focuses on privatization-related ADRs and confirmed that the long-term return performance of emerging market issues is poor. Our findings are consistent with all of these studies.…”
Section: Cross-sectional Regression Of Performance Change On Ownersmentioning
confidence: 95%
“…Schaub (2003) finds that the long-term underperformance of ADRs is greater for IPO issues than for SEO issues, and for emerging market issues than for developed market issues. Aybar (2001) focuses on privatization-related ADRs and confirmed that the long-term return performance of emerging market issues is poor. Our findings are consistent with all of these studies.…”
Section: Cross-sectional Regression Of Performance Change On Ownersmentioning
confidence: 95%
“…For example, Boardman and Laurin (2000) find that privatizations, occurring later in the process, show greater excess positive returns but this variable could equally well proxy agency, asymmetry or political risk arguments. Aybar (2002) show that emerging market PIPOs underperform developed markets issues. Yet this difference could either support political or agency risk arguments.…”
Section: Theoretical Predictions and Previous Findingsmentioning
confidence: 97%